Engaging Paul Ricoeur’s work on memory, history, and forgetting : in search of an adequate methodology for church and theological historiography - Van Tonder, Helene (Stellenbosch : Stellenbosch University, 2010)
Thesis (MTh)--Stellenbosch University, 2010.